2018
DOI: 10.1787/04e36c29-en
|View full text |Cite
|
Sign up to set email alerts
|

The productivity-wage premium

Abstract: This document has been prepared by Giuseppe Berlingieri, Sara Calligaris and Chiara Criscuolo from the Productivity and Business Dynamics (PBD) Division of the OECD Directorate for Science, Technology and Innovation (STI). This draft has benefited from helpful suggestions and feedback from Dirk Pilat, Alexander Hijzen and Isaac Sorkin, as well as WPIA and CIIE delegates, and seminar participants at the AEA Annual Meeting, OECD, and Paris School of Economics. Rudy Verlhac and Isabelle Desnoyers-James provided e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We do see sizeable coefficients in other studies, however. For example, Berlingieri et al (2018a) found dummy values in excess of 1 for large manufacturing firms (250+ employees) in their data. It is interesting to note that the values from Regression 3 with industry-year fixed effects are more similar to those from Regression 1 than was the case for mark-ups.…”
Section: The Impact Of Scale On Multifactor Productivitymentioning
confidence: 99%
“…We do see sizeable coefficients in other studies, however. For example, Berlingieri et al (2018a) found dummy values in excess of 1 for large manufacturing firms (250+ employees) in their data. It is interesting to note that the values from Regression 3 with industry-year fixed effects are more similar to those from Regression 1 than was the case for mark-ups.…”
Section: The Impact Of Scale On Multifactor Productivitymentioning
confidence: 99%